Pricing Issues in Telecommunications - Crandall, Robert (Maine Policy Review, 1994)
Over the last quarter century, significant changes have occurred in telecommunications. The breakup of AT&T and a myriad of technological innovations have sounded the death knell for the theory of telecommunications as a natural monopoly, according to Robert W. Crandall of the Brookings Institute. In the following article, Dr. Crandall assesses a variety of pricing issues that must be addressed by regulators, telecommunications firms and consumers in an increasingly competitive telecommunications market.